Femmes engagées dans la chouannerie : motivations, modalités d’actions et processus de reconnaissance (1794-1830) - Solenn Mabo (Genre & Histoire)
In western France, during the restoration of the French monarchy, between 1825 and 1830, many women from modest backgrounds filed pension applications so that their commitment to the royalist uprising called “chouannerie” (1794-1800) be recognized. In their pension claims, they set out the various forms of their involvement in the civil war. They explained how they took part in the rebellion by giving refuge to the royalist fighters or engaging in other strategic missions. This set of documents is original and relatively unexplored. This documentation may be helpful to examine, from a gender perspective, the process of recognizing the non-combattant commitments. How can one find evidence of an informal involvement that happened long ago ? Did women obtain the same recognition as men for their involvement in the guerrilla movement ? Beyond the issue of recognition, the types of actions led by these women will be examined and their motivations need also to be addressed. The purpose of this paper is to study the specificity of female commitment in the context of the chouannerie and to ponder on the reasons why women were opposing the revolutionary change. Furthermore, this paper raises the difficult issue of the links between resistance, commitment and emancipation.